2013
DOI: 10.1097/mcg.0b013e31829e7edf
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Manifestations, Diagnosis, and Management of Hereditary Angioedema

Abstract: Abdominal pain is one of the most common conditions in clinical practice and yet a challenging complaint to accurately diagnose due to the vast number of possible etiologies. When other health care providers cannot identify the cause of abdominal pain, gastroenterologists are often looked upon to help solve the diagnostic dilemma. Consequently, it is incumbent upon gastroenterologists to be well versed in the diagnosis and management of not only common but also rare causes of abdominal pain. One such uncommon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 15 publications
1
45
0
1
Order By: Relevance
“…3) [21] with at least 50% of attacks involving the abdomen [44]. If a patient with a prior diagnosis of HAE presents with abdominal pain and/or swelling, gastrointestinal angioedema should be considered in the differential diagnosis, even if the patient has not previously experienced similar attacks [45]. In cases with no prior diagnosis of HAE, a differential diagnosis is much more difficult.…”
Section: Reviewmentioning
confidence: 99%
“…3) [21] with at least 50% of attacks involving the abdomen [44]. If a patient with a prior diagnosis of HAE presents with abdominal pain and/or swelling, gastrointestinal angioedema should be considered in the differential diagnosis, even if the patient has not previously experienced similar attacks [45]. In cases with no prior diagnosis of HAE, a differential diagnosis is much more difficult.…”
Section: Reviewmentioning
confidence: 99%
“…1,8,10,11 In Turkey, the diagnostic delay is more than twice what has been reported in the most recent European survey, and is as high as 26 years. 9 Considering these data, it is clear that improvements in the diagnosis of HAE are necessary worldwide.…”
Section: Discussionmentioning
confidence: 85%
“…5,6 The rarity of the disease, together with frequent misdiagnosis of the symptoms as allergic/anaphylactic angioedema, acute abdominal disorder or Familial Mediterranean Fever (FMF), means that while HAE symptoms often begin in early childhood and persist throughout patients' lives, awareness of the condition is extremely low and diagnosis is frequently delayed. [7][8][9] Failure to recognize HAE and to establish a correct diagnosis is well documented. 1,6,10,11 In a recent international survey it has been reported that patients visited an average of 4.4 different physicians for their symptoms before their condition was properly diagnosed.…”
mentioning
confidence: 99%
“…These patients are very likely to be referred to a Gastroenterologist at some point, particularly given that abdominal symptoms occur in approximately 80% of patients [14] and on average it takes 10 years from the time of onset of symptoms until a diagnosis is made [2]. It is commonplace for HAE-mediated abdominal pain to be mistaken for other causes of abdominal pain, such as appendicitis, cholecystitis and small bowel obstruction [15,16].…”
Section: Discussionmentioning
confidence: 99%